(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to evaluate the improvement of swallowing function using the GUSS and identify related factors in patients with Parkinson’s disease after rehabilitation intervention. Subjects: Thirty-five patients with Parkinson’s disease treated at the National Geriatric Hospital from September 2024 to September 2025. Method: A non-controlled interventional study was conducted. Swallowing ability was assessed using the GUSS score before and after a dysphagia rehabilitation program. The intervention included oral-pharyngeal exercises, safe swallowing techniques, and posture training during eating, all performed under the supervision of physicians and rehabilitation therapists. Results: The mean GUSS score increased from 12.97 ± 3.95 to 14.31 ± 3.93, with an average improvement of 1.34 points (p < 0.001). No statistically significant differences in GUSS improvement were observed across age, gender, disease severity, or disease duration groups. Conclusion: After 3 weeks of rehabilitation intervention significantly improved swallowing ability and eating safety in patients with Parkinson’s disease, demonstrating high clinical effectiveness and practical applicability